How has COVID-19 impacted cancer screening? Adaptation of services and the future outlook in Australia - Eleonora Feletto; Paul Grogan; Carolyn Nickson; Megan Smith; Karen Canfell (Sax Institute, 2020)
The coronavirus disease 2019 (COVID-19) pandemic has caused major disruptions to many aspects of life in Australia and globally. This includes actual and potential future impacts on Australia's three national screening programs for breast, bowel and cervical cancer. These programs aim to improve cancer outcomes through an organised approach to the early detection of cancer and precancer in asymptomatic populations. The design of each program varies according to biological differences in the three cancers, the available screening technology, the target population, and variations in their administration of Australia's federal, state and territory jurisdictions. The observed and potential impacts of COVID-19 on these programs, and on related activities such as the current national enquiry into lung cancer screening feasibility, therefore vary significantly. This article focuses on observed short-term impacts, adaptations and the longer-term outlook for cancer screening in relation to COVID-19. It summarises potential responses to minimise the harms of disruptions caused by COVID-19, and highlights research and policy opportunities in the pandemic response and recovery which could inform and accelerate optimisation of cancer screening in the long term.